(untitled) (ENTHYMEMA, 2009)
The article moves in the direction of an intertextual narratology integrating semiotic reflection with logic, focusing on the concept of “configuration” as model of comprehension (Mink, Ricoeur). The concept of “intertextual frames” makes it possible to approach the act of reading interpreting it as abduction process; through this process the Model Reader (Eco) finds in his intertextual encyclopedia the so-called “frames”, that is, basic structures, more or less recognizable in every narrative. With his reading of Lolita the author outlines the interpretative act as abduction process in which “intertextual frames” often recur; in this way, it is possible to single out the paths that a critical reading should not only follow but also open.